1999
DOI: 10.1095/biolreprod60.2.534
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Bovine Pre-Morula-Stage In Vitro Matured/In Vitro Fertilized Embryos after Delipidation and before Use in Nucleus Transfer

Abstract: We have determined that the tolerance of in vitro matured/in vitro fertilized (IVM/IVF) bovine embryos to cryopreservation at the pre-morula stage can be improved by removal of cytoplasmic lipid droplets by centrifugation. Nucleus transfer was also performed using cryopreserved, delipated (lipid droplets removed) 8- to 16-cell-stage blastomeres of IVM/IVF embryos as donor nuclei. In vitro developmental ability of the delipated embryos to the blastocyst stage (20 of 126) was found to be equal to that of undelip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 30 publications
2
43
1
1
Order By: Relevance
“…Such problems are not encountered after blastocyst expansion when, coincident with significant increases in energy needs, blastocyst neutral lipid content is reduced (Nagashima et al, 1992). Physical removal of excess lipid from ova of cattle (Tominaga et al, 1998;Ushijima et al, 1999) and pigs (Nagashima et al, 1994) at earlier developmental stages also reduces sensitivity to chilling. Moreover, Ferguson and Leese (1999) reported that triglyceride concentrations in cattle embryos remain stable from the two-cell to the blastocyst stage in vivo (32.2 versus 33 ng per embryo), whereas in vitro, in embryos exposed to serum (10%, v/v) from the four-cell stage, the triglyceride reserves can double by the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…Such problems are not encountered after blastocyst expansion when, coincident with significant increases in energy needs, blastocyst neutral lipid content is reduced (Nagashima et al, 1992). Physical removal of excess lipid from ova of cattle (Tominaga et al, 1998;Ushijima et al, 1999) and pigs (Nagashima et al, 1994) at earlier developmental stages also reduces sensitivity to chilling. Moreover, Ferguson and Leese (1999) reported that triglyceride concentrations in cattle embryos remain stable from the two-cell to the blastocyst stage in vivo (32.2 versus 33 ng per embryo), whereas in vitro, in embryos exposed to serum (10%, v/v) from the four-cell stage, the triglyceride reserves can double by the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, post-thaw survival of bovine blastocysts was improved after removal of lipid droplets at an earlier stage [18][19][20]. However, Ushijima et al [19] r e p o r t e d t h a t c y t o c ha l a s in t r ea t m e n t a nd centrifugation without micromanipulation did not improve the cryotolerance of bovine zygotes or embryos. We have investigated the effect of polarization of lipid droplets on cryotolerance of 16-cell stage embryos without micromanipulation.…”
Section: Cytoplasmic Lipids Responsible For Cryoinjurymentioning
confidence: 92%
“…Likewise, Nagashima et al [215] demonstrated that the high lipid content of pig embryos was responsible for their higher chilling sensitivity and also that embryos delipidated by centrifugation and microaspiration of polarized lipids became more tolerant to chilling. The lipid content was also pointed out as responsible for the chilling and freezing sensitivity of IVP cattle embryos, and when lipid droplets were displaced by ultracentrifugation (mechanical delipidation), their cryosurvival was improved [216,217]. On the contrary, Romão et al [8] found a reduced viability in IVP sheep embryos submitted to an ultracentrifugation process mostly due to zona pellucida and membrane fracture.…”
Section: Methods Of Improving the Cryopreservation Of Sheep Embryosmentioning
confidence: 99%